A mystery of a cup of coffee; an insight look by chemist. (14th June 2017) - Karpinska, Joanna; Świsłocka, Renata; Lewandowski, Włodzimierz
Abstract: Fruits, vegetables as well as processed food products of plant origin are a rich source of beneficial for human health constituents. Among them the polyphenols constitute a large group of compounds. The presented literature survey is devoted to chlorogenic acid the most abundant representative of cinnamate acids esters. Its chemical as well as biological properties are described. © 2017 BioFactors, 43(5):621–632, 2017